Assessing vertical transmission of SARS-CoV-2 in high-rise apartments via a joint epidemiologic and modeling investigation - Chong, Samuel Z.; Ooi, Chin Chun; Abdul Malek, Muhammad Ismail Bin; Ge, Zhengwei; Low, Derrick; Kang, Chang Wei; Chiew, Calvin J.; Chae, Sae-Rom; Teoh, Yee Leong; Tan, Kelvin Bryan (Frontiers in Public Health, 2025)
High-rise apartments (HRAs) present a complex environment with multiple routes of infection, especially for respiratory pathogens like SARS-CoV-2. With HRAs serving as the dominant housing modality in many dense urban regions worldwide, particularly in dense Asian cities such as Singapore, where high-rise living is normative, understanding transmission within such settings is essential for both global and region-specific public health preparedness. In this study, we assessed transmission risks and potential routes of transmission within HRAs based on observed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) clusters in Singapore. We analyzed SARS-CoV-2 incidence in HRAs subjected to government-mandated mass screenings to evaluate the transmission risk associated with various relative positions within an HRA and found significantly elevated risk of transmission for residents living within the same vertical stack as a potential index case. A computational fluid dynamics (CFD) model was further developed for an HRA with the highest vertical transmission risk to elucidate potential routes of aerosol transmission. Interestingly, the epidemiological analysis indicated an increased risk of infection for residents living within two levels above an infected case, correlating with CFD observations that aerosolized particles can move vertically up the stack and remain at elevated concentrations in the two levels above a potential index case. The analysis and modeling provide additional insights into alternative vertical transmission within HRAs, distinct from prior studies that have primarily hypothesized transmission via drainage stacks. Nonetheless, factors such as wind direction and individual unit configurations are shown in CFD to have a significant influence on the potential spread of aerosolized particles in such settings, highlighting the need for additional in-depth investigation. This study further demonstrates the importance of joint epidemiology and numerical modeling to better understand different potential mechanisms of particle spread, especially in the HRA setting.